Dyslipoproteinemic changes in borderline hypertension. - Lemne, C; Hamsten, A; Karpe, F; Nilsson-Ehle, P; de Faire, U (1994)
The present study examined plasma lipoprotein, lipoprotein lipase, hepatic lipase, and insulin levels in men with borderline hypertension (diastolic blood pressure 85 to 94 mm Hg) compared with age-matched normotensive control subjects (diastolic blood pressure less than or equal to 80 mm Hg, n = 75 + 75). High-density lipoprotein (HDL) subclasses were determined in a subset (n = 45 + 45). While total and low-density lipoprotein cholesterol levels were similar, levels of very-low-density lipoprotein (VLDL) cholesterol and triglycerides (0.46 versus 0.41 mmol/L, P = .027, and 1.0 versus 0.85 mmol/L, P = .031) and total triglycerides (1.53 versus 1.33 mmol/L, P = .009) were elevated and HDL cholesterol was reduced in the borderline group compared with the normotensive group (1.17 versus 1.26 mmol/L, P = .043). The HDL subclass HDL2b concentration was lower (0.16 versus 0.24 mmol/L, P = .006), while HDL3b and HDL3c concentrations were higher in the borderline group (0.38 versus 0.32 mmol/L, P = .016, and 0.19 versus 0.16 mmol/L, P = .042). Significantly higher activities of hepatic lipase in the borderline group (282 versus 232 mU/mL, P = .024) and significant correlations between lipoprotein lipase activity and VLDL and HDL concentrations suggest an involvement of these enzymes in the development of these differences. When adjusted for body mass index or insulin level, all differences disappeared, except for HDL3b and HDL3c concentrations, which remained significantly elevated. These results indicate that dyslipoproteinemic changes are present in early hypertension. Although most of these changes are related to obesity, alterations in HDL profile were not explained by influences of body mass index and insulin.